2020
DOI: 10.1177/0892705720930787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mussel shell reinforcement on mechanical and tribological behavior of polyphenylene sulfide composites

Abstract: Polyphenylene sulfide (PPS) is commonly used in automobile industry, aeronautics and space electrical–electronic components, and mechanical applications. Mussel shell wastes could be an economical reinforcement alternative for polymer-based composites. Which also gets out the environmental trouble of mussel shell wastes. To examine the effect of mussel shell wastes as reinforcing material, particulate mussel shell wastes were incorporated into the PPS matrix in different mass ratios (0, 1, 3, 5, and 10 wt%). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Insufficient matrixreinforcement interaction causes agglomeration of the particles and the formation of large interfaces. 8,20 As a result, interparticle stress transfer cannot occur successfully and causes a decrease in material strength. 59 Within the scope of this study, due to the surface modification process, the interface interaction between the polymer and reinforcement increased, thus increasing the tensile strength.…”
Section: Tensile Test Resultsmentioning
confidence: 99%
“…Insufficient matrixreinforcement interaction causes agglomeration of the particles and the formation of large interfaces. 8,20 As a result, interparticle stress transfer cannot occur successfully and causes a decrease in material strength. 59 Within the scope of this study, due to the surface modification process, the interface interaction between the polymer and reinforcement increased, thus increasing the tensile strength.…”
Section: Tensile Test Resultsmentioning
confidence: 99%
“…Due to the high particle matrix interface, the loss of mass gradually increases with the particle being displaced during scratching. 35,61…”
Section: Scratch Test Resultsmentioning
confidence: 99%
“…This equation represents whether the scratch mechanism occurred in the form of plastic deformation or ploughing. Figure 3 shows the scratch track diagram [35][36][37]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyphenylene sulfide matrix was used to produce particulate mussel shell waste-reinforced composites (0–10 wt %) [ 34 ]. The authors showed that all composites show better adhesive wear resistance compared to neat matrix, with the best results obtained for the composites filled with the lowest weight percentage of waste, i.e., 1 wt %.…”
Section: Agricultural Waste Materialsmentioning
confidence: 99%